Dietary administration of probiotics to sows and/or their neonates improves the reproductive performance, incidence of post‐weaning diarrhea and histopathological parameters in the intestine of weaned piglets. (28th March 2016) - Hayakawa, Teruo; Masuda, Tomohide; Kurosawa, Daisuke; Tsukahara, Takamitsu
Abstract: Probiotics have gained considerable attention with respect to their beneficial effects on livestock performance and health. The most significant effects of probiotics on the gut microbiota and the host animals take place when they are included in diets during particularly stressful periods such as weaning and/or at the beginning of the lactation period. The probiotics Bacillus mesentericus strain TO‐A at 1 × 10 8 colony forming units (CFU)/g, Clostridium butyricum strain TO‐A at 1 × 10 8 CFU/g and Enterococcus faecalis strain T‐110 at 1 × 10 9 CFU/g were used. Litter weight at delivery and ratio of return to estrous improved significantly (17% and 24% improvement, respectively) by probiotic administration to sows (0.2% (w/w)). Furthermore, the feed intake of the probiotics‐administered sows was greater than that of the control sows during the late lactation period. Post‐weaning diarrheal incidence and growth performance was improved by probiotics administration to neonates (0.02% (w/w)), while the combined use of probiotics in sows and their neonates induced the enlargement of villous height and prevented muscle layer thinning in the small intestine of weaning piglets. The administration of probiotics of three species of live bacteria improved the porcine reproductive performance around stressful periods of sows (farrowing) and piglets (weaning). [Corrections added on 26 April 2016, after first online publication: ' Enterococcus faecalis strain T‐100' has been corrected to ' Enterococcus faecalis strain T‐110' in the above paragraph and in the 'Probiotics' section under the Materials and Methods heading.]